Konsep Keadilan dan Sistem Tanggung Jawab Keperdataan dalam Hukum Udara - Ahmad Sudiro (Fakultas Hukum Universitas Islam Indonesia, 2012)
The research studies and analyzes the settlement of the indemnification to passengers due to flight accident. The scope of the research involves the obligation of the airlines company, aircraft producer, and insurance company in settling the indemnification to passengers who die, are injured, or disabled due to flight accident in Indonesia using liability theory. This research uses normative law method with qualitative approach which is explanatory and evaluative in form to find the solution to a problem by applying descriptive analysis. The result of the research concludes that, first, the indemnification to the passengers who die, are injured, or disabled due to flight accident is based on the principles of absolute liability. Second, the indemnification from insurance company to the passengers as the first party insurance is paid as the amount of the indemnification incurred as stated in the insurance agreement, based on the premium paid.